Producing a gypsum-based self-leveling mortar for subfloor modified by polycarboxylate admixture (PCE). (18th January 2023) - Silva, D.B.P.; Lima, N.B.; Lima, V.M.E.; Estolano, A.M.L.; Nascimento, H.C.B.; Vilemen, P.; Padron-Hernández, E.; Carneiro, A.M.P.; Lima, N.B.D.; Povoas, Y.V.
Highlights: PCE clearly increased the flowability of gypsum-based mortars. PCE delayed the initial and final setting times of gypsum mixtures. The hydration heat of the mixtures decreased as PCE content increased. There was a decrease on mechanical properties as PCE content increased. Changes on morphology caused by PCE were observed using SEM. Abstract: Self-leveling mortar is a layer applied on a surface without the need for thickening. This type of mortar has large fluidity and is often cement-based, with low productivity. The production of a self-leveling gypsum-based mortar provides shorter execution times, as well as better thermal and acoustic properties and eliminates the need for expansion joints in large areas. This article aims to develop a gypsum-based mortar with self-leveling properties for application in the subfloor layer. In this sense, water/gypsum ratios of 0.45, 0.475, and 0.5 were used, in addition to plaster/sand ratios of 1:1 and 1:0.5 for each consistency. The content of superplasticizer additive (PCE) was adjusted to consistency suitable for self-leveling through the fluidity test. The set of mortars were characterized by considering tests of fluidity, enthalpy of hydration, setting times, compressive and flexural strength, and experiments of scanning electron microscopy (SEM). The results revealed that the PCE increased the setting times, reduced the water content, and modified the crystalline structure of the dihydrate. Finally, the mortar with water/gypsum ratio of 0.5, gypsum/sand ratio 1: 0.5 and 1% PCE presented satisfactory properties, with the exception of setting times.